The Influence of Agile Strategies and Methods on MSMES in Indonesia - Chandra Hosen (IJHCM (International Journal of Human Capital Management), 2022)
This study is based on the importance of MSMEs in Indonesia, since they have their own role in economic development, specifically in their ability of absorbing labor. On the other hand, there is changing situation of MSMEs in Indonesia due to post Covid-19 Pandemic. Therefore, the purpose of this study is to measure the influence of Agile Strategies and Methods on MSMEs in Indonesia, using quantitative method. This study takes data from one of the businesses or MSMEs in Indonesia as main core of influence research and presents the results of responses from various MSMEs (only 30 businesses) and company position holders, as validation of the findings on the business that became the study. Furthermore, from 60 employees in one of the MSMEs from a total of 30 MSMEs as research object, the results showed that Agile strategies and methods have significant influence to improve employee performance in MSMEs in Indonesia, such as working faster, performing better, increasing productivity, effective working, making work easier, and usefully affecting employee performance. The writer concluded that the use of agile methods has an influence on performance of business organizations and research interprets that their use is able to improve performance, productivity, save costs, and of course as a matter of nature, become more flexible and agile to develop.